Simultaneous Presbyopia and Astigmatism Correction with a Novel Trifocal Toric Intraocular Lens-A One-Year Follow-Up - Nováček, Ladislav Viktor; Němcová, Marie; Sičová, Kristýna; Tyx, Kateřina; Rozsíval, Pavel; Němčanský, Jan; Studený, Pavel (Journal of clinical medicine, 2022)
The current investigation evaluates the efficiency of the trifocal toric Liberty 677MTY intraocular lens (IOL) in correcting preoperative corneal astigmatism in cataract patients demanding spectacle independence. The retrospective evaluation included 28 eyes of 15 patients with preoperative corneal astigmatism of at least 1.0 Dioptre (D). All patients were followed up for one year postoperatively. Residual refractive errors and visual acuities at multiple distances were measured. Binocular visual acuity and contrast sensitivity defocus curves were plotted. Visual functions and patient satisfaction were assessed. The efficiency of astigmatism correction was determined using the vector analysis method. The mean spherical equivalent refraction (SEQ) improved from 2.72 ± 1.62 D to 0.10 ± 0.48 D. The cylindric refraction decreased from 1.18 ± 0.45 D to 0.16 ± 0.31 D. Vector analysis proved efficient astigmatism correction with a centroid of 0.10 ± 0.34 D at 161°. Ninety-two percent of eyes resulted within 0.5 D from the target refraction. Visual acuities were 0.1 logMAR or better from +1.0 to -3.5 D defocus values. Visual tasks could be performed without major difficulties. Our patients were highly satisfied. Refractive and visual outcomes with the investigated presbyopia-correcting toric IOL are predictable and the lens provides excellent trifocal vision.
Keywords: presbyopia; cataract; astigmatism correction; intraocular lens; rotational stability; toric; trifocal